HUBUNGAN TINGKAT STRESS DAN GAYA HIDUP TERHADAP KEJADIAN HIPERTENSI PADA LANSIA DI DESA KEMAMANG BALEN BOJONEGORO - Roni, Faishol; Bagus, Nanang; Fitriani, Eka Diah (WELL BEING, 2018)
Entering old age is slow and progressive human will lose the resistance to infection so that the susceptible exposed degenerative diseases. Hypertension is one of the degenerative diseases that often occur. The hypertension is the disease that is called "silent killer". Two of some risk factors the causes of hypertension are stress and lifestyle. The purpose of the research is to analyze the correlation between stress levels and lifestyle compored with the case of hypertension incidance at elderly. This research employed correlation with cross sectional approach. The sampling applied purposive sampling that involved 25 respondents. For data correlation, questionnaires were used to research on the stress and lifestyle, and observation sheet was used to measure the blood pressure to research on the hypertention incidance. The result of this research showed stress levels had significance values (p)=0,001, lifestyle obtained significant value (p)=0,003. There is a correlation between stress levels and lifestyle in the elderly with hypertention.